Sex and age distributions of persons in foodborne disease outbreaks and associations with food categories. (2019) - Strassle, P. D.; Gu, W.; Bruce, B. B.; Gould, L. H.
Abstract: Sex and age differences in food preferences may be reflected in the demographics of outbreaks. Outbreaks from 1998–2015 with a single confirmed implicated food source in the Centers for Disease Control and Prevention Foodborne Disease Outbreak Surveillance System were analysed using logistic regression to assess associations between a food category, sex and age. Males were more likely to be involved in outbreaks attributed to beef, pork, game, dairy and shellfish; females were more likely to be involved in grains-beans, nuts-seeds, fruits, sprouts and vegetable row crops outbreaks. Children <5-years-old were more likely than other age groups to be involved in dairy outbreaks, children 5–19-years-old were most likely to be involved in beef and game outbreaks, adults 20–49-years-old were most likely to be involved in fish, shellfish and sprout outbreaks and adults ⩾50-years-old were most likely to be involved in turkey outbreaks. Age and sex are associated with specific food categories in outbreaks. This information may be useful in helping to identify sources of foodborne disease outbreaks.